Exploring cultural preservation and innovation: augmented reality packaging prototyping for the Mah Meri tribe in Malaysia - Santano, Delas *; Maslisa, Zainuddin *; James, Melissa Ann Marie (IEEE, 2024)
This paper delves into the intersection of cultural preservation and technological innovation through the lens of a research-creation project centered on the Mah Meri tribe in Malaysia. The project focuses on the development and implementation of augmented reality (AR) packaging prototyping as a means to safeguard and promote the rich cultural heritage of the Mah Meri community. The Mah Meri tribe, residing in the coastal areas of the Malaysian peninsula, possesses a unique cultural identity characterized by intricate wood carvings, traditional dances, and elaborate rituals. However, like many indigenous communities, the Mah Meri face challenges in preserving and transmitting their cultural practices to future generations amidst rapid globalization and modernization. AR offers a promising avenue for cultural preservation by blending the physical and digital realms to enhance user engagement and learning experiences. In this project, AR enabled packaging prototypes were designed to showcase Mah Meri artifacts, stories, and rituals in an interactive and immersive manner. By scanning the packaging with a mobile device, users can access augmented content such as 3D models, audio narratives, and visual animations that provide contextual information and insights into Mah Meri culture. Through a reflective inquiry approach, this paper explores the conceptualization, design process, and implementation of the AR packaging prototypes, as well as the insights gained from engaging with members of the Mah Meri community. Furthermore, the paper discusses the potential implications of AR technology for indigenous communities beyond the Mah Meri tribe, highlighting opportunities for collaboration, knowledge exchange, and cultural revitalization. By bridging traditional practices with contemporary innovations, this research-creation project exemplifies a holistic approach to cultural preservation that respects indigenous knowledge systems while embracing technological advancements in a rapidly changing world.